2020
DOI: 10.1016/j.xpro.2020.100097
|View full text |Cite
|
Sign up to set email alerts
|

Co-culture Systems of Drug-Treated Acute Myeloid Leukemia Cells and T Cells for In Vitro and In Vivo Study

Abstract: SUMMARY A combination of immunotherapy and chemotherapy strategies could strengthen antitumor effects. This protocol elucidates a robust method via co-culturing drug pre-treated acute myeloid leukemia cells with CD3 + T cells, derived from leukoreduction system chambers, for in vitro and in vivo study. We optimized several aspects of the procedures, including timing of drug treatment, quantification of tumor cells, and approach of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…For the co-cultures, A549 cells (10 5 cells/well) were seeded at the bottom and THP-1 cells (10 5 cells/well) were plated on the insert (0.4 μm pore polyester filter) of Transwell culture plates (#3470, Corning Inc., Corning, NY, USA), with the two cell cultures being physically separated to avoid direct contact, according to the method described by Li et al [ 32 ]. After 24 h co-culture, the cells were exposed to the following treatments: vehicle (DMSO 0.5% in PBS), CsA_rm 10 µg/mL, CsA_M20 at 10 µg/mL in respect to CsA, mannitol 2 µg/mL in DMSO 0.5% in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…For the co-cultures, A549 cells (10 5 cells/well) were seeded at the bottom and THP-1 cells (10 5 cells/well) were plated on the insert (0.4 μm pore polyester filter) of Transwell culture plates (#3470, Corning Inc., Corning, NY, USA), with the two cell cultures being physically separated to avoid direct contact, according to the method described by Li et al [ 32 ]. After 24 h co-culture, the cells were exposed to the following treatments: vehicle (DMSO 0.5% in PBS), CsA_rm 10 µg/mL, CsA_M20 at 10 µg/mL in respect to CsA, mannitol 2 µg/mL in DMSO 0.5% in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…This co-culture assay allows us to test the effects of various drug combinations and study the innate mechanisms, which influence the immune response. Moreover, it could also help in understanding the combined effect of immunotherapy and chemotherapy [ 46 ]. The same research group reported that AML cells when pre-treated with FTO inhibitors, CS1 or CS2 and co-cultured with activated T cells, resulted in the increased killing of AML cells along with decreased expression of LILRB4 [ 47 ].…”
Section: Introductionmentioning
confidence: 99%